Assessing the Modulatory Effects of tDCS and Acupuncture on Cerebral Blood Flow in Chronic Low Back Pain Using Arterial Spin Labeling Perfusion Imaging - Valeria Sacca; Nasim Maleki; Sveta Reddy; Sierra Hodges; Jian Kong (Brain Sciences)
Background: Both transcranial direct current stimulation (tDCS) and acupuncture are promising methods for managing chronic low back pain (cLBP), however, their underlying mechanisms remain unclear. Methods: To explore the neural mechanisms of tDCS and acupuncture on cLBP, we examined how real and sham tDCS applied to the bilateral motor cortex (M1), combined with real or sham acupuncture, influenced cerebral blood flow (CBF) using pulsed continuous arterial spin labeling (pCASL) imaging. tDCS was administered over six sessions, combined with real or sham acupuncture, over one month. Results: Following real tDCS, we observed increased CBF in the bilateral occipital cortex, precuneus, left hippocampus, and parahippocampal gyrus/posterior cingulate cortex. After sham tDCS, CBF decreased in regions including the bilateral superior parietal lobule, precuneus, bilateral precentral and postcentral gyri, and left angular gyrus. Real acupuncture led to reduced CBF in the bilateral occipital cortex and hippocampus, and left posterior cingulate gyrus, and increased CBF in the right postcentral gyrus, superior parietal lobule, and frontal areas. Sham acupuncture was associated with decreased CBF in the bilateral hippocampus and anterior cingulate gyrus. Conclusions: These results suggest both shared and distinct patterns of CBF changes between real and sham tDCS, as well as between real and sham acupuncture, reflecting mode-dependent effects on brain networks involved in pain processing and modulation. Our findings highlight the different neural circuits implicated in the therapeutic mechanisms of tDCS and acupuncture in the management of cLBP.